ETHNOPOLITICAL PROCESSES IN THE ROSTOV REGION, THE KRASNODAR AND STAVROPOL TERRITORIES: PROBLEMS, CONTRADICTIONS, AND PROSPECTS - MARKEDONOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2005)
Ethnopolitical processes in the so-called Russian regions of the Caucasus should be studied not only for academic but also for practical purposes. All students of the Caucasus concentrate either on Chechnia or the armed conflicts in Abkhazia, Nagorny Karabakh, South Ossetia, etc. Experts tend to pay attention to the latent conflicts in the North Caucasian republics and the South Caucasian states (the conflicts in Karachaevo-Cherkessia and Kabardino-Balkaria, the Lezghian question, the Armenian-Georgian relations in Samtskhe-Ja vakheti). The Rostov Region and the Krasnodar and Stavropol Territories, however, on the whole have so far remained outside the scope of the expert community’s attention. In fact, the geopolitical and socioeconomic role of the so-called Russian regions of the North ern Caucasian can hardly be overestimated. Together, the three federation constituencies cover 68.5 percent of the Russian Northern Caucasus, while their 12 million-strong population comprises 68.35 percent of the total North Caucasian population and 8.25 percent of Russia’s population. The Krasnodar Territory is the third in Russia where its population size is concerned; it comes after Moscow and the Moscow Region. The Rostov Region is the sixth among the 89 RF constituencies, with Moscow, the Moscow Region, the Krasnodar Territory, St. Petersburg, and the Sverdlovsk Region having larger populations. The Krasnodar Territory boasts of the Black Sea coast with large recreation centers of international importance: Sochi populated by about 345,000 and Novorossiisk with the population of 189,000. The latter also has terminals for the Azeri and Kazakhstani oil and gas. The Novorossiisk and Tuapse ports are the country’s first and third freight haulage centers. In the future the Krasnodar Territory will become the main Black Sea naval base of the RF. Rostov-on-Don is the capital of sorts of the North Caucasian Military District (the only one in the country involved in hostilities). The ecological resorts of the Caucasian Mineral Waters set up in 1993 by a presidential decree 1 is part of the Stavropol Territory. At the same time, the Stavropol Territory is found in the very heart of the Russian Caucasus and its ethnopolitical landscape, and borders on the seats of the most complicated ethnic conflicts (Chechnia, North Ossetia, and Daghestan). The Krasnodar and Stavropol territories and the Rostov Region are Russia’s largest grain producers that ensure the country’s food security. The Russian North Caucasian regions are very important at the time of federal elections: today there are 18 deputies of the State Duma elected in single-member districts (the Krasnodar Territory and the Rostov Region are represented by seven deputies each, while the Stavropol Territory has four deputies). This shows that the future of Russia’s policies in the Great er Caucasus, its security in the south and across the country depend, to a great extent, on continued stability, ethnic harmony and prevention of conflicts in the Russian regions of the Northern Caucasus.